Evaluation of Ractopamine HCl feeding programs on growth performance and carcass characteristics of finishing pigs - W Ying; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 934 barrows and gilts (PIC 337 × 1050, initially 240 lb) were used in a 26-d experiment to evaluate the effect of different Ractopamine HCl (RAC) feeding programs on growth and carcass traits of finishing pigs. Treatments included a basal diet with (1) no RAC for 26 d (control), (2) 7.5 ppm RAC for 26 d (constant), (3) 5 ppm RAC for d 0 to 14 and 10 ppm for d 14 to 26 (step-up), and (4) RAC concentration increased daily from 5 ppm on d 0 to 10 ppm on 26 d by using the FEEDPro (Feedlogic Corp., Willmar, MN) system (curve). Each treatment had 10 pens with a similar number of barrows and gilts in each pen. From d 0 to 14, pigs fed diets containing RAC had greater (P<0.001) ADG and better (P<0.001) F/G than those fed the control diet. Pigs fed the constant or step-up RAC feeding methods had greater (P<0.04) ADFI compared with those fed the control diet. From d 14 to 26, all RACfed pigs had greater (P<0.001) ADG and better (P<0.001) F/G than control pigs. Overall, pigs fed diets containing RAC had improved (P<0.001) ADG and better F/G than pigs fed the control diet. Pigs fed the step-up RAC program had greater (P = 0.01) ADG and better (P = 0.02) F/G than the constant RAC program. Pigs marketed on d 14 and 26 had heavier (P<0.001) HCW when fed diets containing RAC compared with control pigs. Pigs fed constant RAC had greater (P = 0.002) carcass yield than control pigs. Pigs fed the constant RAC program also had greater (P = 0.03) loin depth on d 14 than control pigs. No differences were found in carcass traits among RAC treatments. Feeding RAC improved performance regardless of feeding method, but few differences were present among the RAC feeding programs in carcass weights or measurements.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; Feeding program; Finishing pig; Growth; Ractopamine HCl